A Requirements-Based Taxonomy of Software Product Line Evolution - Schmid, Klaus; Eichelberger, Holger (Electronic Communications of the EASST, 2008)
Software product lines are, by their very nature, complex software systems.Due to the interconnectedness of the various products in the product line any form of evolution becomes significantly more complex than in a single system situation. So far most work on product line evolution has focused on specific approaches to supporting special cases of the evolution problem. In this paper, we take a different approach and provide a broad taxonomy of requirements-driven evolution in software product lines. This serves as a basis for the identification of requirements on evolution support.